Genome-wide analysis of AP2/ERF family in Akebia trifoliata and characterization of an AtrERF001 gene regulate fruit ripening - Niu, Juan; Li, Ying; Sun, Zhimin; Lin, Ying; Zhang, Chao; Yang, Bo; Tian, Shuang; Luan, Mingbao (Frontiers in Plant Science, 2025)
IntroductionEthylene response factors (ERF) were important for plant growth, hormone signaling, fruit ripening and stress response. Despite the wide identification of ERF family members in various species, limited information is available regarding this family in Akebia trifoliata.MethodsThe APETALA2/ethylene response factor genes in A. trifoliata were identified and analyzed using bioinformatic approaches and AtrERF001 was verified to be involved in fruit ripening by experiments.ResultsTherefore, 131 APETALA2/ethylene response factor genes were identified from the A. trifoliata genome. Gene structures, motif compositions, tandem duplication events and promoter structure of ERF genes were characterized, providing insights into the molecular basis underlying the discrepant functions of ERF genes within each evolutionary branch. Expression patterns under ethylene and 1-MCP treatments of these ERF genes were further analyzed using real-time PCR (RT-qPCR), revealing that 9 key ERF genes are closely associated with fruit ripening. A co-expression regulatory network analysis indicated that AtrERF001 was one of the hub gene. AtrERF001 was found to localize in nucleus by subcellular localization analysis. Overexpression of AtrERF001 in Akebia trifoliata and tomato fruit resulted in early fruit ripening. The expression levels of AtrERF001, AtrACO and AtrPE in overexpression fruits were increased by about 30-fold, 5-fold and 1-fold, respectively, compared with the control, whereas silencing of AtrERF001 in A. trifoliata by virus induced gene silencing showed opposite trends. Moreover, RT-qPCR experiments showed that the expression of AtrERF001, AtrACO and :AtrPE in AtrERF001 overexpression tomato fruits at red-ripe stage were significantly increased compared with the control fruits, indicating that AtrERF001 may play an important role in regulating fruit ripening.DiscussionOur results provide new insights into the underlying regulatory mechanisms of the AP2/ERF family during fruit ripening.